2015
DOI: 10.1007/s10953-015-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

FeCl3 Based Imidazolium Ionic Liquids as Novel Solvents for Extractive–Oxidative Desulfurization of Liquid Fuels

Abstract: FeCl 3 based imidazolium ionic liquids were synthesized and employed as novel solvents in extractive desulfurization for removal of dibenzothiophene, thiophene, benzothiophene, 3-methylthiophene, and 4,6-dimethyldibenzothiophene in model fuel. FeCl 3 based ionic liquids such as 1-butyl-3-methylimidazolium chloride iron chloride [C 4 MIM]Cl/FeCl 3 , 1-octyl-3-methylimidazolium chloride iron chloride, didecyldimethyl ammonium chloride iron chloride, ammonium tributyl-methyl chloride iron chloride, and trioctyl-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…In contrast, KO 2 , which is a solid oxidant, can be maintained at high concentrations and is stable and safe even at high purity . Apart from the disadvantages of the oxidants, it was claimed that the rate of desulfurization could scale up by increasing the oxidant concentration Table presents the effect of the use of oxidants on desulfurization .…”
Section: Desulfurization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, KO 2 , which is a solid oxidant, can be maintained at high concentrations and is stable and safe even at high purity . Apart from the disadvantages of the oxidants, it was claimed that the rate of desulfurization could scale up by increasing the oxidant concentration Table presents the effect of the use of oxidants on desulfurization .…”
Section: Desulfurization Methodsmentioning
confidence: 99%
“…Extractive desulfurization (EDS) is a promising technology and has a simple process because it can be utilized at ambient temperature and pressure. , Since the operating parameters for EDS are ambient temperature and pressure and there is no need to consume hydrogen in this method, extractive desulfurization is considered as one of the most efficient methods. , In other words, not requiring a catalyst or any other materials during the process and needing normal circumstances to be done, ,,, EDS seems to be more applicable than other desulfurization methods. ,, Thus, EDS has received a lot of attention because it needs simple and normal operating conditions. In this regard, Table has been provided to indicate the advantages and disadvantages of the EDS process compared to the other investigated desulfurization methods.…”
Section: Desulfurization Methodsmentioning
confidence: 99%
“…Dharaskar and co-workers used a 1:1 (Bmim)Cl/FeCl 3 mixture and found that 59.2% of thiophene (Th) was extracted. 4 The authors proposed a specific interaction between thiophene and the Fe III -based anion. Li et al 5 and Yang et al 6 studied the adsorption of thiophene using a Ag + or Cu + −Y zeolite.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dharaskar and co-workers used a 1:1 (Bmim)­Cl/FeCl 3 mixture and found that 59.2% of thiophene (Th) was extracted . The authors proposed a specific interaction between thiophene and the Fe III -based anion.…”
Section: Introductionmentioning
confidence: 99%
“…). To investigate the effects of several operating parameters on the oxidative sulfur reduction process, various mixtures of immiscible solutions (CA-Lewis acid-Fe(III) halide) in diesel fuel were made up for oxidation with H 2 O 2 and which played a triple role in the process of sulfur removal.Ferric chloride has a pronounced effect on the extraction of organo S-compounds from oil products Dharaskar et al, 2015,. noted that due to the specific interaction between the Fe 3+ cation and aromatic sulfur compounds, up to 59% of sulfur species could be extracted into the Lewis acidic FeCl 3 -based (Bmim)Cl phase.…”
mentioning
confidence: 99%